Resenha de MAURER, Bill; MUSARAJ, Smoki; SMALL, Ivan (eds.). 2019. Money at the Margins: Global Perspectives on Technology, Financial Inclusion and Design. New York: Berghahn Books - Perin, Vanessa Parreira (Revista de Antropologia da UFSCar, 2021)
Resenha de MAURER, Bill; MUSARAJ, Smoki; SMALL, Ivan (eds.). 2019. Money at the Margins: Global Perspectives on Technology, Financial Inclusion and Design. New York: Berghahn Books